Pharmacist Goes to School: Promoting DAGUSIBU As A Pharmaceutical Education Tool for Adolescents - Saputra, Yoga Dwi; Ulya, Tuhfatul; Hasina, Raisya; Aini, Siti Rahmatul; Puspitasari, Candra Eka; Andanalusia, Mahacita; Lisnasari, Baiq Risky Wahyu; Hamdin, Candra Dwipayana (Jurnal Gema Ngabdi, 2024)
Drug misuse is an urgent public health issue, often arising from a lack of knowledge about proper medication use. Research shows that over half of the medications worldwide are used irrationally. The DAGUSIBU program (Dapatkan, Gunakan, Simpan, Buang or known as Get, Use, Store, Dispose) was developed as a solution to address this issue by providing education on proper medication management. This community service activity was organized by the Pharmacy Study Program and the Pharmacy Professional Education Program (PSPPA), Faculty of Medicine and Health Sciences (FKIK), Universitas Mataram, on August 9, 2024, at Kesuma Catholic High School in Mataram. The primary goal of this activity was to teach students the correct ways to obtain, use, store, and dispose of medications, as well as to introduce the pharmacist profession and the Pharmacy program at UNRAM to high school students. The activity included interactive presentations on DAGUSIBU, an introduction to the pharmacist profession, and a quiz competition as an evaluation method. The quiz encouraged active student participation, with prizes to boost motivation. Despite challenges such as varying levels of student comprehension and time constraints, the activity successfully improved students’ understanding of rational drug use and introduced career opportunities in pharmacy. Overall, this activity proved effective in raising student awareness and knowledge, positively impacting their health literacy.